ANALISIS KESULITAN BELAJAR FISIKA PADA PESERTA DIDIK DALAM MEMAHAMI KONSEP TEKANAN ZAT: Bahasa Indonesia - Askaria; Stepanus Sahala Sitompul; Firdaus Firdaus (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
The aim of this research is to find out the students difficulty of learning physics on understanding the substance pressure concept in junior high school 4 Sungai Raya. This research is a quantitative research in surveying related research with a simple descriptive method with 31 sample of students. The instrument used was a four tier diagnostic test, totaling 6 questions. The data of the test results was then analyzed to calculate the percentage of physics difficulties that students experience in understanding the concept of liquid pressure, to calculate the percentage of each category of concept understanding, and to knowing what it is learning difficulties at any problem. Based on the results of the study showed the percentage of learners who understood the concept of lower 9,14% compared wiht students of the misconception of 54,94% and did not understand the concept of 36,02%. Based on the data analysis was concluded that it is still a high percentage of learning difficulties experienced by students. Any learning difficulties students can be known from each indicator of concept understanding. This research is expected to be used as a consideration of further research